Ratio of hemocomponents in massive transfusion and mortality of trauma patients in a university hospital - Mercado del Angel, Felipe; Cazares Tamez, Rogelio; Díaz Olachea, Carlos Gabriel; Pérez Chávez, Fernando (UANL. Facultad de Medicina, 2014)
Background: Nowadays, there are very few studies about massive transfusion in our country. This situation generates the necessity to the elevation of possible new strategies to diminish mortality and its adverse effects. Material and methods: All massive transfusions were evaluated in a retrospective way from October 2010 to October 2012. All diagnosis groups were recorded and the patients were divided into three groups depending on the ratio between packed red blood cells (PRBC) and fresh frozen plasma (FFP) units (ratios ≤2, >2, and without FFP). Their mortality and/or survival were evaluated 30 days after as well as all the factors associated with the event. Results: A total of 69 patients were included (37 trauma patients, 28 gunshot wounds and 4 with lacerated wounds); the groups (ratios ≤2, >2, and no plasma at all) were distributed as follows: 30, 30 and 9 patients each, with an overall mortality rate of 60.8% within 30 days. A lower survival rate (12%) in the no plasma group (P=.015) was found and systolic blood pressure during transfusion had a mean of 67.7 mmHg (P=.012) in this group. Fresh frozen plasma units were 136 and 249 for >2 and ≤2 ratios respectively (P<.01); 85.5% of all patients developed metabolic acidosis during the transfusion, and the number of days in the hospital after the event had a mean of 24.5 days in all patients. Conclusions: High rates of massive transfusion mortality are still being reported in our ield. The use of transfusion strategies contribute to elevate the survival rate in patients with massive transfusion treatment